2016
DOI: 10.1021/acs.macromol.6b01519
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Imaging of Functionalized and Polymer-Grafted Graphene Oxide

Abstract: We investigate the surface and subsurface morphology of stearylamine-modified graphene oxide sheets and polystyrene-grafted functionalized graphene oxide sheets through atomic force microscopy (AFM) operated in multi-set point intermittent contact (MUSIC) mode. This allows a depth-resolved mapping of the nanomechanical properties of the top surface layer of the functionalized graphene oxide sheets. On the surface of stearylamine-functionalized graphene oxide sheets, we can distinguish areas of hydrophilic grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The phase shift signal was used to generate subsurface images of polymeric materials. 318,319 The hydration of biopolymers under different conditions was followed by recording phase shift-distance curves. 320,321 Several viscoelastic processes on polymer blends and polymer nanocomposites have been studied by AFM phase contrast images.…”
Section: The Paradox Of Afm Phase-imagingmentioning
confidence: 99%
“…The phase shift signal was used to generate subsurface images of polymeric materials. 318,319 The hydration of biopolymers under different conditions was followed by recording phase shift-distance curves. 320,321 Several viscoelastic processes on polymer blends and polymer nanocomposites have been studied by AFM phase contrast images.…”
Section: The Paradox Of Afm Phase-imagingmentioning
confidence: 99%
“…The reconstructed MUSIC-mode AFM images are free from feedback loop artifacts and allow for quantitative and depth-resolved imaging of soft polymeric surfaces with unprecedented spatial resolution and detail. 22,44,45,[52][53][54] Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work on reassembled type I collagen fibrils, we showed that AFM imaging in air with controlled humidity restores the fibril’s water content and allows high-resolution imaging. , We also learned how the attractive capillary tip–sample interaction can be discriminated from a fibril’s viscoelastic response . In studies of polymeric nanostructures, we constructed 3D depth profiles of the local tip–sample interaction from maps of APD data. Roduit et al showed how depth-resolved stiffness profiles can be constructed from FD data. Here, we employ these AFM-based 3D depth-profiling techniques to study native (unfixed) tendons.…”
mentioning
confidence: 99%